Making sense of leadership and language styles of student leaders in a Malaysian public secondary school - Syed Shaharuddin, Sharifah Syakila; Harun, Minah (Issues in Language Studies, 2022)
Language plays an essential role in everyday experiences, given that it can facilitate and maintain congenial relationships if it is used properly. Not much is known about how young student leaders make sense of their communicative acts with their peers, especially in the Malaysian context. The study investigated student leaders' sensemaking of leadership and language use in a public secondary school in Northern Malaysia. Their narratives were obtained through a qualitative study using focus groups and face-to-face in-depth interviews. The findings revealed several themes that explain the preferred spoken language styles among the student leaders in performing their responsibilities at school. The study demonstrated that appropriate language use should be part of the training of student leaders at school or leadership training curriculum for secondary school leaders nationwide. In that way, the student leaders will not only be exposed to proper language use in communicating leadership, but they will also be motivated to polish up and reflect on their language use for continuous self-development.